2017
DOI: 10.1111/joor.12464
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement in removable prosthodontics: a literature review

Abstract: Removable prosthodontics are often associated with mechanical troubles in daily use, such as fracture or deformation. These troubles render prostheses unusable and reduce wearers' QOL. Various reinforcements are used to prevent such problems, but consensus on reinforcement has not been reached. This review aimed to summarise the effects of reinforcement and to propose favourable reinforcement based on material, design and position in the prostheses. Initially, 139 articles were selected by electronic and manua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
(217 reference statements)
0
16
0
Order By: Relevance
“…A recent literature review on overdenture reinforcement concluded that cast metal reinforcement was most effective in improving the mechanical properties of the prostheses, for both strength and rigidity. The reinforcement should be placed around the deformable and stress‐concentrating areas such as the occlusal surface of the copings/roots in overdenture prostheses to reduce the incidence of fracture . However, the aim of reinforcement is not solely to prevent denture base fracture, but also to enhance functional rigidity for occlusal stability, and to distribute the masticatory load to the underlying denture‐supporting areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent literature review on overdenture reinforcement concluded that cast metal reinforcement was most effective in improving the mechanical properties of the prostheses, for both strength and rigidity. The reinforcement should be placed around the deformable and stress‐concentrating areas such as the occlusal surface of the copings/roots in overdenture prostheses to reduce the incidence of fracture . However, the aim of reinforcement is not solely to prevent denture base fracture, but also to enhance functional rigidity for occlusal stability, and to distribute the masticatory load to the underlying denture‐supporting areas.…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al observed that the greatest strain exists beneath the overdenture surface close to the top of each coping . Clinical studies have recommended overdenture reinforcements to improve the mechanical properties of prostheses . Despite rapid development in overdenture attachments and implant‐supported overdentures, overdentures with metal copings remain a viable and usable modality in dental practice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first attempts to reinforce acrylic plates of removable dentures consisted in the introduction of steel screws to dentures to prevent cracking, which only resulted in complicated repair thereof [3,[6][7][8]. The use of glass fibers to reinforce resins opened new possibilities of acrylic compound reinforcement [9].…”
Section: Ocena Wytrzymałości Mechanicznej Poli(metakrylanu Metylu) Wzmentioning
confidence: 99%
“…It has been shown that RODs require extensive maintenance to prevent them from technical (e.g. chipping fractures or loss of retention) [19,20] and/or biological (e.g. recurrent caries or periodontal disease) complications [21,22].…”
Section: Introductionmentioning
confidence: 99%